2020
DOI: 10.1155/2020/3596384
|View full text |Cite
|
Sign up to set email alerts
|

The New Fertility Policy and the Actuarial Balance of China Urban Employee Basic Endowment Insurance Fund Based on Stochastic Mortality Model

Abstract: This study aims to investigate the impact of China’s new fertility policy on the actuarial balance of its Urban Employee Basic Endowment Insurance (UEBEI) fund, with stochastic mortality model included to address the longevity risk. Combined with the latest UEBEI policy, this paper constructs an actuarial balance model and introduces the growth rate of wage, the age of employment and the age of retirement, the rate of payment, the rate of replacement, the annual rate of pension adjustment, and the population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The results showed that all the key assumptions passed the robustness test. As mentioned in the literature review, few scholars in China have conducted indepth research on the relationship between fertility policy adjustments and UEBMI fund sustainability [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that all the key assumptions passed the robustness test. As mentioned in the literature review, few scholars in China have conducted indepth research on the relationship between fertility policy adjustments and UEBMI fund sustainability [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with URRBMI, the sustainability concerns regarding the UEBMI fund have attracted more attention from scholars, and the forecast horizon of much of this research is 2050. These studies concluded that the adjustment of the fertility policy could delay the occurrence of the deficit of the UEBMI fund and reduce the deficit amount to a certain extent; this has been generally recognized by scholars [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…ough these reforms could enhance the financial sustainability, it is unlikely to completely settle the problem of inadequate solvency of pension funds (Xie et al [3]; Zeng and Yu [4]). Meanwhile, the Chinese government also considers extending the mandatory retirement age and implementing the collection system reform.…”
Section: Introductionmentioning
confidence: 99%
“…Although China's UEBPI system does not stipulate the government's contribution responsibility, the government still provides fiscal subsidies to the provinces with an annual deficit in funds. Zheng [3] suggested that fiscal subsidy should be fixed at a certain level, so that the pension system could achieve a balanced development by itself. According to "Statistical Bulletin on the Development of Human Resources and Social Security," the fiscal subsidy accounted for 18%-21% of the UEBPI fund's expenditure from 2015 to 2019, with an average value of 20.17%.…”
Section: Optimization Scenario 3: Introducing External Financementioning
confidence: 99%
“…Some studies have considered the impact of longevity risk. Xie et al [25] aimed to investigate the impact of China's new fertility policy on the actuarial balance of its CEBPS fund, with a stochastic mortality model included to address longevity risk. Zhao et al [26] built a comprehensive risk assessment system to evaluate the solvency sustainability of CEBPS by integrating the Lee-Carter model into their population projection.…”
Section: Introductionmentioning
confidence: 99%